Communication for development in Africa - Robert Agunga (Communicare)
A major concem about African development is not so much that the war on povelfy is far from being won but because the practice of development administrators lacks professionalism. Calls for involving beneficiaries in democratic project decision making, for conducting systematic social science research as the basis for external intervention, and for building the capacities of indigenous officials to reduce national dependence on expatriate expertise have gone unheeded. Development policies, nowadays are sound but until these are properly carried out poverty eradication will be impOSSible. The paper argues that it will require development communication expertise to cany out the above policies and hence the need for development support communication experts in development programming. The paper examines the promise DSC has for making projects work better and urges donor agencies to incorporate it into their projects.